Interfaces
The mission of Interfaces is to publish manuscripts focusing on the practice of operations research and management science and the impact this practice has on organizations throughout the world. The most appropriate papers are descriptions of the practice and implementation of OR/MS in commerce, industry, government, or education. The journal publishes papers in all areas of OR/MS including operations management, information systems, finance, marketing, education, quality, and strategy. Comments on published material and on how Interfaces can better serve its readers are solicited.